Rethinking Terra Nullius and Property Law in Space - Wian Erlank (Potchefstroom Electronic Law Journal, 2015)
With a new era dawning with regard to access to space and an increase in the number of nations capable of reaching and exploiting space, the field of space law as a whole needs to be re-evaluated. One such area where current legal thinking needs to be examined is with regard to the property rights to objects in space. While it was sufficient in the past for governments to frown upon the institutions of ownership in outer space and leave many space-related issues unresolved, one would need to re-examine the current body of space-law and related international instruments in the light of the ability of private enterprises’ and other new players’ ability to partake in and commercially exploit space travel. This paper investigates whether property rights should be available to space-faring nations and individuals, as well as how these rights could be acquired. Also very important is how these rights could be limited or structured in such a way as not to unnecessarily interfere with the aims of current space law. Characteristics such as the impersonality, tangibility, independence, susceptibility to control, and the usefulness and value for mankind of an object in space will once again be of crucial importance when it is necessary to determine if it can be classified as an object with regard to which one can have property rights. This is discussed against the background of objects that are deemed to be res nullius (things belonging to nobody) as well as the theory of terra nullius (land belonging to nobody).